First-generation scholar in Indonesian indigenous family tribe: economic, social, and cultural capital - Ahmad Juhaidi; Analisa Fitria; Noor Hidayati; Ridha Fadillah (Institute of Advanced Engineering and Science, 2024)
Indigenous tribe students have difficulty in their education. Only a few of them managed to complete the tertiary level. This study aims to explore and understand deeply the efforts made by these first scholars in obtaining educational economic, social and cultural capital. This research is qualitative research with a phenomenological approach to understand deeply the economic, social and cultural capital of scholars from the Dayak Meratus Tribe. The data were collected through interviews with 17 participants such as first- generation scholars in the family, their parents, and teachers. The results showed that economic capital was built by parents through great effort on gardening, farming, and trading. Meanwhile, the social and cultural capital built by parents was very limited. Social capital and cultural capital are provided by the extended family, communities and non-profit institutions. Role of school is very limited to build social and cultural capital. The study recommends school administrators implement professional development programs for teachers and counsellors to improve their competence in building student social and cultural capital. Government should decide a policy to support indigenous tribe education not just financial support, but social and cultural capital support, and job opportunity for them in their community.